STRATEGI REBRANDING ELEMENTS PADA UMKM DAPOER MENENG UNTUK MENINGKATKAN BRAND AWARENESS (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Currently, many micro, small and medium enterprises have emerged in the food sector, one of which is Dapoer Meneng. Dapoer Meneng is an MSME from Bandung that was founded in 2020. This brand has a problem that is not too well known by the public, therefore we are rebranding the Dapoer Meneng brand by changing several brand elements that aim to improve brand identity. The things that have been done are changing the logo, suggesting new packaging forms, having a color palette as a characteristic, adding and using contemporary language, adding thank you cards and labels and also creating more creative and flexible promotional content. This has received a positive response, both from the owner and from the community. What we do has the same ultimate goal, namely to build a brand identity which we hope can grow brand awareness to consumers and also increase sales from the Dapoer Meneng itself.